A hard carbon material and preparation method thereof, and sodium ion battery

The preparation of hard carbon materials by pre-carbonization and high-temperature heat treatment methods has solved the problem of excessive specific surface area and pores of biomass hard carbon materials in the prior art, and improved the capacity of sodium ion batteries and the efficiency of the first Coulomb.

CN117342537BActive Publication Date: 2025-04-11SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311241045.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-04-11
Estimated Expiration
2043-09-22

AI Technical Summary

Technical Problem

The specific surface area and pores of biomass hard carbon materials prepared by the prior art lead to low capacity of sodium ion batteries and first-time Coulomb efficiency.

Method used

Hard carbon materials are prepared by pre-carbonization and high-temperature heat treatment to form a unique hierarchical porous structure, retaining the advantages of the original fiber pores of litchi wood material, and providing a continuous conductive three-dimensional network skeleton.

Benefits of technology

The processing performance and electrochemical performance of hard carbon negative electrode materials are improved, the first Coulomb efficiency and circulation capacity are enhanced, and the embedding and removal of sodium ions and the penetration of electrolyte are suitable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117342537B_ABST
    Figure CN117342537B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of sodium batteries, and specifically relates to a method for preparing a hard carbon material, comprising: providing a litchi wood powder material; in an inert gas atmosphere, subjecting the litchi wood powder material to a carbonization treatment to obtain a semi-finished product; subjecting the semi-finished product to a heat treatment to obtain the hard carbon material; and the temperature of the heat treatment is 1000-1700°C. The preparation method provided by the present invention has a wide biomass source, low cost and stable structure. By controlling the temperature, heating rate and insulation time of carbonization and heat treatment, the prepared porous carbon material has a suitable graphitization degree and stacking gap, which is more suitable for the embedding and extraction of sodium ions and the penetration of electrolytes, so that the obtained hard carbon material exhibits excellent sodium storage performance, and improves the capacity and first-cycle coulomb efficiency of sodium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention specifically relates to a hard carbon material and a preparation method thereof, and belongs to the technical field of sodium ion battery material preparation. Background Art

[0002] In recent years, lithium-ion batteries have been developed rapidly in portable electronic devices, resulting in an increase in the consumption of lithium resources year by year. Faced with problems such as the scarcity of lithium resources, these problems are difficult to be solved through technological improvements. Sodium and lithium belong to the main group of alkali metals and have similar physical and chemical properties. At the same time, compared with metallic lithium, the reserves of sodium in the earth's crust are greater (about 2.64%), which is about 400 times the reserves of lithium. In addition, the extraction of metallic sodium is simpler, easier to obtain, and cheaper. Since the radius of sodium ions is larger than that of lithium ions, they cannot be embedded in graphite.

[0003] Currently, carbon-based negative electrode materials are mostly used to store sodium to improve the performance of sodium-ion batteries. However, the specific surface area and pores of biomass hard carbon materials prepared by existing technologies are too large, resulting in low capacity and first coulombic efficiency.

[0004] Therefore, the prior art still needs to be optimally improved and enhanced. Summary of the invention

[0005] One of the purposes of the present invention is to provide a method for preparing a hard carbon material, which can remove impurities only after pre-carbonization without the need for acid washing and other steps. The target product has a unique hierarchical porous structure compared to other hard carbon materials. After simple pre-carbonization and high-temperature heat treatment, it not only retains the advantages of the original fiber pores of the lychee wood material, but also provides a three-dimensional network skeleton that can conduct electricity continuously, thereby accelerating the ion transmission dynamics and ion exchange dynamics. The hard carbon negative electrode material prepared has a small specific surface area and porosity, so that the hard carbon negative electrode material has good processing performance, excellent electrochemical performance, high first coulomb efficiency and high cycle capacity.

[0006] In order to achieve the above-mentioned purpose, the following technical solution is provided.

[0007] In a first aspect, a method for preparing a hard carbon material comprises:

[0008] Provide litchi wood powder material;

[0009] In an inert gas atmosphere, the litchi wood powder material is subjected to a carbonization treatment to obtain a semi-finished product;

[0010] The semi-finished product is heat-treated to obtain the hard carbon material; the heat treatment temperature is 1000-1700° C., such as 1000-1100° C., 1100-1200° C., 1200-1300° C., 1300-1400° C., 1400-1500° C., 1500-1600° C., 1600-1700° C. By controlling the heat treatment temperature at 1000-1700° C., the original fiber pore advantage of the litchi wood material is retained, and a continuous conductive three-dimensional network skeleton can be formed inside the litchi wood.

[0011] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0012] As a preferred technical solution, the method for preparing the hard carbon material, wherein the temperature of the primary carbonization treatment is 800-1000°C, such as 800-850°C, 850-900°C, 900-950°C, 950-1000°C. The primary carbonization is carried out in a flowing protective gas atmosphere, and the hard carbon material is obtained after the litchi wood is subjected to the primary carbonization treatment. The primary carbonization can better decompose and gasify the organic polymer lignin, cellulose and hemicellulose, and volatilize the organic carbon and semi-coke to obtain hard carbon.

[0013] As a preferred technical solution, in the method for preparing the hard carbon material, the holding time of the heat treatment is 2 to 5 hours, such as 2 hours, 3 hours, 4 hours, and 5 hours.

[0014] As a preferred technical solution, in the method for preparing the hard carbon material, the particle size of the litchi wood powder material is ≤600 mesh.

[0015] As a preferred technical solution, the method for preparing the hard carbon material, wherein the providing of litchi wood powder material comprises:

[0016] Cutting the litchi wood to obtain litchi wood segments;

[0017] The litchi wood segments are dried, pre-carbonized and crushed to obtain litchi wood powder material; the temperature of the pre-carbonization is 300-550°C. For example, the litchi wood is cut into litchi wood segments with a length of 15 cm and a radius of 5 cm, and the litchi wood segments are placed in a blast drying oven at 80°C for 48 hours. In a flowing protective atmosphere, the temperature is 450°C for pre-carbonization, and after the pre-carbonization is completed, the litchi wood segments are crushed into powder with a particle size less than 600 meshes by a crusher.

[0018] As a preferred technical solution, in the method for preparing the hard carbon material, the heat preservation time of the pre-carbon treatment is 3 to 5 hours.

[0019] As a preferred technical solution, in the method for preparing hard carbon material, the heating rate of the primary carbonization treatment is 1-6°C / min. The carbonization treatment can be made more uniform by controlling the heating rate.

[0020] As a preferred technical solution, in the method for preparing the hard carbon material, the inert gas is selected from at least one of argon, helium, nitrogen and neon.

[0021] In a second aspect, a hard carbon material is provided, wherein the hard carbon material is prepared by the preparation method described above.

[0022] In a third aspect, a sodium ion battery comprises a negative electrode material, wherein the negative electrode material is the hard carbon material described above.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The preparation method provided by the present invention has a wide biomass source, low cost and stable structure. By controlling the temperature, heating rate and holding time of carbonization and heat treatment, the prepared porous carbon material has a suitable degree of graphitization and stacking gap, which is more suitable for the embedding and extraction of sodium ions and the penetration of electrolyte, so that the obtained hard carbon material exhibits excellent sodium storage performance, thereby improving the capacity and first-cycle coulomb efficiency of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 X-ray diffraction patterns of LZM-1000, LZM-1200, LZM-1400, LZM-1500, LZM-1600 and LZM-1700 sample powders prepared in Examples 1 to 6 of the present invention.

[0026] Figure 2 Scanning electron microscope images of LZM-1200, LZM-1400, LZM-1500 and LZM-1600 sample powders prepared in Examples 1 to 6 of the present invention.

[0027] Figure 3 Raman spectra of LZM-1000, LZM-1200, LZM-1400, LZM-1500, LZM-1600 and LZM-1700 sample powders prepared in Examples 1 to 6 of the present invention.

[0028] Figure 4 This is a comparison chart of the first cycle charge and discharge curves of LZM-1000, LZM-1200, LZM-1400, LZM-1500, LZM-1600 and LZM-1700 prepared in Examples 1 to 6 of the present invention at 0.2C.

[0029] Figure 5 The cyclic voltammetry test diagram of LZM-1600 prepared in Examples 1 to 6 of the present invention at a scanning voltage range of 0.001 to 3 V and a scanning rate of 0.1 mV / S. DETAILED DESCRIPTION

[0030] The present invention is further described below in conjunction with specific examples. It should be noted that the reagents, materials and instruments used in the following examples are all commercially available unless otherwise specified.

[0031] Example 1

[0032] Litchi wood cut into 10 cm in length and 5 cm in radius was placed in a forced air drying oven and dried at 80°C for 48 h. The dried lychee wood was placed in a tubular furnace filled with argon and kept warm at 300°C for 5 h with a heating rate of 1°C / min. The pre-carbonized lychee wood was crushed into 500-mesh powder material using a pulverizer.

[0033] The obtained powder material was placed in a graphite crucible for primary carbonization, and then placed in a tubular furnace filled with argon gas and kept at 800°C for 2 hours at a heating rate of 5°C / min to obtain a hard carbon material.

[0034] The obtained hard carbon material was placed in a graphite crucible for high-temperature heat treatment, and was placed in a tubular furnace filled with argon gas and kept at 1000°C for 2 hours with a heating rate of 5°C / min to obtain the hard carbon material, which was named LZM-1000.

[0035] Example 2

[0036] Litchi wood cut into 10 cm in length and 5 cm in radius was placed in a forced air drying oven and dried at 80°C for 48 h. The dried lychee wood was placed in a tubular furnace filled with argon and kept warm at 300°C for 5 h with a heating rate of 1°C / min. The pre-carbonized lychee wood was crushed into 450-mesh powder material using a pulverizer.

[0037] The obtained powder material was placed in a graphite crucible for primary carbonization, and then placed in a tubular furnace filled with argon gas and kept at 800°C for 2 hours at a heating rate of 3°C / min to obtain a hard carbon material.

[0038] The obtained hard carbon material was placed in a graphite crucible for high-temperature heat treatment, and was placed in a tubular furnace filled with argon gas and kept at 1200°C for 2 hours with a heating rate of 3°C / min to obtain the hard carbon material, which was named LZM-1200.

[0039] Example 3

[0040] Litchi wood cut into 10 cm in length and 5 cm in radius was placed in a forced air drying oven and dried at 80°C for 48 h. The dried lychee wood was placed in a tubular furnace filled with argon and kept at 300°C for 5 h with a heating rate of 1°C / min. The pre-carbonized lychee wood was crushed into 300-mesh powder material using a pulverizer.

[0041] The obtained powder material was placed in a graphite crucible for primary carbonization, and then placed in a tubular furnace filled with argon gas and kept at 800°C for 2 hours at a heating rate of 2°C / min to obtain a hard carbon material.

[0042] The obtained hard carbon material was placed in a graphite crucible for high-temperature heat treatment, and was placed in a tubular furnace filled with argon gas and kept at 1400°C for 2 hours with a heating rate of 4°C / min to obtain the hard carbon material, which was named LZM-1400.

[0043] Example 4

[0044] Litchi wood cut into 10 cm in length and 5 cm in radius was placed in a forced air drying oven and dried at 80°C for 48 h. The dried lychee wood was placed in a tubular furnace filled with argon and kept at 300°C for 5 h with a heating rate of 1°C / min. The pre-carbonized lychee wood was crushed into 300-mesh powder material using a pulverizer.

[0045] The obtained powder material was placed in a graphite crucible for primary carbonization, and then placed in a tubular furnace filled with argon gas and kept at 800°C for 2 hours at a heating rate of 4°C / min to obtain a hard carbon material.

[0046] The obtained hard carbon material was placed in a graphite crucible for high-temperature heat treatment, and was placed in a tubular furnace filled with argon gas and kept at 1500°C for 2 hours with a heating rate of 4°C / min to obtain the hard carbon material, which was named LZM-1500.

[0047] Example 5

[0048] Litchi wood cut into 10 cm in length and 5 cm in radius was placed in a forced air drying oven and dried at 80°C for 48 h. The dried lychee wood was placed in a tubular furnace filled with argon and kept warm at 300°C for 5 h with a heating rate of 1°C / min. The pre-carbonized lychee wood was crushed into 350-mesh powder material using a pulverizer.

[0049] The obtained powder material was placed in a graphite crucible for primary carbonization, and then placed in a tubular furnace filled with argon gas and kept at 800°C for 2 hours at a heating rate of 5°C / min to obtain a hard carbon material.

[0050] The obtained hard carbon material was placed in a graphite crucible for high-temperature heat treatment, and was placed in a tubular furnace filled with argon gas and kept at 1600°C for 2 hours with a heating rate of 5°C / min to obtain the hard carbon material, which was named LZM-1600.

[0051] Example 6

[0052] The lychee wood cut into 10 cm in length and 5 cm in radius was placed in a forced air drying oven and dried at 80°C for 48 hours. The dried lychee wood was placed in a tubular furnace filled with argon and kept warm at 300°C for 5 hours with a heating rate of 1°C / min. The pre-carbonized lychee wood was crushed into powder material below 200 mesh using a pulverizer.

[0053] The obtained powder material was placed in a graphite crucible for primary carbonization, and then placed in a tubular furnace filled with argon gas and kept at 800°C for 2 hours at a heating rate of 5°C / min to obtain a hard carbon material.

[0054] The obtained hard carbon material was placed in a graphite crucible for high-temperature heat treatment, and was placed in a tubular furnace filled with argon gas and kept at 1700°C for 2 hours with a heating rate of 5°C / min to obtain the hard carbon material, which was named LZM-1700.

[0055] The hard carbon materials prepared in Examples 1 to 6 were tested, and their X-ray diffraction patterns were as follows: Figure 1 As shown. From the XRD curve, it can be seen that the position of the diffraction peak shifts with the increase of carbonization temperature, the position of the (002) diffraction peak shifts to the right with the increase of carbonization temperature, and the position of the (100) diffraction peak shifts to the left with the increase of carbonization temperature. According to the Bragg equation 2dsinθ=nλ, it is calculated that the d(002) interlayer spacing of the litchi wood material decreases with the increase of carbonization temperature, but it is much larger than the graphite interlayer spacing of 0.34nm. The larger interlayer spacing can easily allow Na+ to be embedded in the hard carbon material. According to the Scherrer formula, the grain size La and the graphite layer stacking thickness Lc of the hard carbon material increase with the increase of carbonization temperature. The increase of Lc indicates that more graphite layers can store more Na+. The higher the carbonization temperature, the clearer the (100) diffraction peak. It shows that the structure of the hard carbon material tends to be ordered with the increase of carbonization temperature. Figure 2 This is a scanning electron microscope image of the hard carbon material prepared in the above example. Figure 2 It can be seen that the porous carbon materials prepared by pre-carbonization and high-temperature heat treatment all have appropriate graphitization degree and stacking gap. Figure 3 It can be seen that the Raman spectrum shows that the area ratio of the D peak to the G peak (ID / IG) of the carbon sample at high pyrolysis temperature decreases with the increase of carbonization temperature, further confirming the trend of orderly transformation of the carbon structure. Figure 4The first charge and discharge curves of LZM at different carbonization temperatures can be seen in the figure. It can be seen from the figure that the carbonization temperature has a great influence on the first charge and discharge curve of LZM. With the increase of carbonization temperature, the reversible specific capacity of LZM1000, LZM1200, LZM1400, LZM1500, LZM1600, and LZM1700 increases, which are 167.52 mAh g -1 , 269.35mAh g -1 and 321.54mAh g -1 , 324.46mAh g -1 、349.82mAh g -1 and 317.71mAh g -1 At the carbonization temperature of 1600 °C, LZM1600 exhibits the highest specific capacity of 349.82 mAh g -1 .from Figure 5 It can be seen that the CV curve is the most accurate reflection of the electrochemical reaction between the LZM electrode and sodium. Figure 5 The CV curve of the LZM electrode in the first three weeks at a carbonization temperature of 1600°C, with a scan rate of 0.1mV / s and a scan voltage range of 0.001-3V. There is a pair of sharp redox peaks at around 0.1V. The redox peaks correspond to the release and insertion of Na+. The CV curves in the first three weeks have good repeatability, indicating that the material has good structural stability and good cycle performance.

[0056] Example 7

[0057] 1. Assemble the battery:

[0058] Take 80 mg of sample (product prepared in each example), add 10 mg of polyvinylidene fluoride (PVDF), 10 mg of conductive carbon black (Super P), and then add 400 μL of N-methylpyrrolidone (NMP), stir for 15 min to obtain slurry, apply it on the surface of aluminum foil, and dry to obtain a negative electrode.

[0059] The electrolyte is an ester electrolyte, and 1M sodium perchlorate (NaClO4) is dissolved in ethylene carbonate / diethyl carbonate electrolyte (EC / DEC, v:v=1:1). The counter electrode is a sodium sheet.

[0060] The above-mentioned negative electrode plate, electrolyte and sodium plate are used to assemble a button battery.

[0061] 2. Test:

[0062] Discharge specific capacity: Discharge to 0.005V at 0.2C constant current, 1C = 100mAh / g.

[0063] Charging capacity: Charge to 3.0V at 0.2C constant current.

[0064] First-cycle coulombic efficiency: charge specific capacity / discharge specific capacity.

[0065] The test results are shown in Table 1.

[0066] Table 1

[0067]

[0068] It can be seen from Table 1 that the preparation of hard carbon materials using the method of the present invention can effectively improve the capacity and initial efficiency of sodium ion batteries.

[0069] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. Application of litchi wood in preparing negative electrode materials for sodium ion batteries; The negative electrode material comprises a hard carbon material, and the preparation method of the hard carbon material comprises: The litchi wood was cut into segments with a length of 10 cm and a radius of 5 cm, and dried in a forced air drying oven at 80°C for 48 hours; The dried litchi wood segments were placed in a tubular furnace with argon gas and kept at 300°C for 5 h at a heating rate of 1°C / min for pre-carbonization. The pre-carbonized lychee wood is crushed into a 350-mesh powder material using a crusher; The powder material is placed in a graphite crucible for primary carbonization, and then placed in a tubular furnace filled with argon gas and kept at 800° C. for 2 h at a heating rate of 5° C. / min to obtain a semi-finished product; The semi-finished product is placed in a graphite crucible for high-temperature heat treatment, and is placed in a tubular furnace filled with argon gas and kept at 1600° C. for 2 hours at a heating rate of 5° C. / min to obtain the hard carbon material.

Citation Information

Patent Citations

  • Novel three-dimensional carbon material as well as preparation method and application

    CN108609600A

  • Sodium-ion battery carbon negative electrode material prepared based on waste wood chips and preparation method thereof

    CN113651307A